Effect of Shorea robusta resin extract in 3-nitropropionic acid-induced Huntington's disease symptoms in Sprague-Dawley rats - Chirag Patel; Khushboo Thakur; Lalita Shagond; Sanjeev Acharya; Ketan Ranch; Sai HS Boddu (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Huntington's disease (HD) is a neurodegenerative disease characterized by neuronal death in the striatum. Asiatic acid is an active component of Shorea robusta (Dipterocarpaceae) plants with neuroprotective activity and is considered an acceptable therapeutic candidate for different neurodegenerative diseases. In the present study, the beneficial pharmacological action of Shorea robusta resin extract (SRRE) was assessed in 3-nitropropionic acid (3-NP)-induced HD in rats. Experimental approach: The neuroprotective effect of SRRE (285.7 and 666.7 mg/kg, p.o., 14 days) was studied in 3-NP (10 mg/kg)-induced rats by measuring body weight, behavioral parameters including neurological scoring, motor coordination, spatial memory, and depression-like behavior, neuro-biochemical parameters (gamma-aminobutyric acid and acetylcholinesterase), and oxidative stress parameter in the brain. Histopathology of the rat's brain was also studied. Findings/Results: SRRE treatment (285.7 mg/kg and 666.7 mg/kg) substantially restored body weight, motor coordination, and mitochondrial enzyme complex I function and improved memory impairment as compared to 3-NP-treated rats. Furthermore, SRRE treatment significantly restored the antioxidant enzyme activity in brain tissue and ameliorated the histopathological changes induced by 3-NP. Conclusion and implications: The neuroprotective effect of SRRE on 3-NP-induced HD in rats was mediated by a reduction in oxidative stress which may favor the usefulness of Shorea robusta in HD.